The Teacher's Role as A Motivator in Instilling The Disciplinary Character of Students with Special Needs - Ismuwardani, Zakiyah; Sholeha, Herisa Hardiyanti (FKIP ULM, 2024)
This study aims to analyze the role of teachers as motivators in forming disciplined characters in special needs students in grade 4 of SDN 1 Gunungsari Dalam. This study employed a descriptive method with a qualitative approach to deeply understand the role of teachers in this context. Data collection was carried out through direct observation and unstructured interviews. Observations involved observing daily interactions between teachers and students during learning, while interviews with teachers provided an in-depth understanding of the role of teachers as motivators. The interviewees were one teacher in grade 4 of Elementary School, the principal, and two students with special needs who were the subjects in this study. The study results indicate that students with special needs are granted accommodations during the learning process. In inclusive classrooms, teachers also serve as directors, motivators, and observers. They monitor students' development and offer guidance tailored to each student's requirements and potential. Teachers also establish a positive and inclusive learning environment and motivate students through various methods, such as establishing achievable objectives, dispensing praise, and guiding students based on their interests. Furthermore, the education of children with special needs is significantly influenced by parental support. Parents actively engaged in their children's education can enhance their emotional development and academic performance. At SDN Gunungsari Dalam, parents of students with special needs often communicate with teachers and provide additional support at home. The role of teachers as motivators has proven effective in forming disciplined characters in children with special needs. This study improves discipline in children with special needs and offers a broader range of advantages in inclusive education.